Adaptações curriculares para um aluno com transtorno do espectro do autismo: estudo de caso - Almeida, Giovana Maria de (Universidade Federal de São Carlos, 2021)
Autism is a disorder that affects a person's ability to communicate and interact socially, as well as their learning. This case study analyzes pedagogical actions performed by me as a therapeutic companion for an eleven-year-old child with moderate autism. The objective of this work was to investigate the effects of social and pedagogical adaptations made within the school environment. This is a qualitative research that developed for two years within a private institution in the interior of São Paulo. Through procedures such as describing the proposed activities, identifying the difficulty in both developing such activities, as well as the difficulties and acceptance of the student in relation to them. The analysis and development of the types of evaluation and the inclusion of the child in the classroom. The conclusions indicate a satisfactory development of the student in relation to their communication, the pleasure and interest in developing pedagogical activities and a remarkable increase in socialization.
Curricular adaptations for a student with autism spectrum disorder: a case study
Keywords: Estudo de caso; Inclusão Escolar; Transtorno do Espectro do Autismo; Case study; School inclusion; Autism Spectrum Disorder; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO